TINJAUAN LITERATUR REVIEW KESEIMBANGAN KEHIDUPAN KERJA PADA PEKERJA PEREMPUAN - Zetli, Sri; Susanti, Lusi; Jumeno, Desto (Universitas Putera Batam, 2025)
In recent decades, the share of women in the labor force has increased substantially. Work-life balance is an important issue for both employees/individuals and employers. This article aims to identify and map work-life balance measures of female workers in major scientific databases, through a bibliographic portfolio process and systematic literature review. Elsevier (SCOPUS) and ScienceDirect databases were used in this study. Data analysis was conducted using VOSviewer. The selected bibliographic portfolio consisted of 76 publications in the period 2016-2023. The results show that developed countries have a larger number of publications such as the UK (14 publications), the USA (13 publications), and South Korea (12 publications). The research fields that covered the most work-life balance research were Business, Management, and Accounting (20.6%), Social Sciences (20.6%), Health (19.1%) and only 4.6% for Engineering. International Journal Of Environment Research And Public Health (10 publications) was the source of the most journals that published publications on work-life balance in female workers. Analysis based on the highest keyword is Human (30 occurrences, 24 links, 218 total link strength and average publication in 2020), followed by female (29 occurrence, 24 links, 213 total link strength and average publication in 2020), while for the keyword Ergonomics (5 occurrence, 19 links, 40 total link strength and average publication in 2021). The group of objects widely studied in the discussion of work-life balance is the group of all employees as much as 43%, the group of female workers 23% and employees in the Manufacturing industry only 3%.